Temporal variations in the incompatible trace element systematics of Archean volcanic rocks: Implications for tectonic processes in the early Earth - Sotiriou, Paul; Polat, Ali; Windley, Brian F.; Kusky, Timothy (Precambrian Research, 2022)
Temporal variations in the incompatible trace element geochemistry of volcanic rocks in Archean greenstone belts have major implications for the style of tectonics that operated in the early Earth, and if and when plate tectonic processes occurred in the Archean, which are still subjects of substantial debate. Comparing the geochemistry of Archean volcanic rocks with that of Phanerozoic arc volcanic rocks has the potential to shed light on these questions. Geochemical data from 8,249 Eoarchean to Neoarchean volcanic rocks and 20,099 Phanerozoic arc volcanic rocks were compiled from the literature to address the above questions through the application of temporal incompatible trace element ratio variations, N-MORB-normalised trace element diagrams, and tectonic setting discrimination diagrams. The sampled rocks range in composition from ultramafic through basaltic and andesitic to dacitic/rhyolitic. Most of the incorporated Archean volcanic rocks were deemed to have been unaffected by significant alteration or crustal contamination in the literature and, therefore, to reflect their provenance, a feature that was corroborated by this study. Most of these Archean volcanic rocks plot in the plate margin, oceanic arc and continental arc fields in classification and tectonic setting discrimination diagrams, with the remainder plotting in the alkaline arc, mid-ocean ridge and oceanic island fields. Comparison between N-MORB-normalised trace element diagrams of volcanic rocks from well-studied Archean greenstone belts in Greenland, Canada, South Africa, China, Australia, India, Brazil and Finland and volcanic rocks from well-studied modern arcs demonstrates that their trace element patterns are remarkably similar. This indicates that the former formed in arc-related settings by modern-style plate tectonic processes that operated throughout the Archean. The Pb and Nb anomalies of most Archean volcanic rocks are fully consistent with an arc-related setting. The temporal variations in the incompatible trace element ratios of Archean volcanic rocks, coupled with their lithological associations, demonstrate that intra-oceanic arc magmatism was prominent in the Eoarchean before a shift in these ratios in the Paleoarchean signified the beginning of Andean-style continental arc magmatism between 3500 and 3200 Ma. Modern-style plate tectonic processes were a far more important contributor to Archean crustal growth and evolution than sagduction-driven vertical tectonic processes.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Archean tectonics; Archean volcanic rocks; Modern arc volcanic rocks; Temporal variation; Trace element systematics